2018
DOI: 10.1002/jwmg.21477
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of a giant panda population influenced by land cover

Abstract: The distribution of species and their causes are key questions for population ecology and conservation. Giant pandas (Ailuropoda melanoleuca) in the Daxiangling Mountains, China are part of an isolated population on the edge of the species’ range and little is known regarding their distribution. Based on land cover, topography, human disturbance, and panda occurrence data in 2 national giant panda surveys, we used a species distribution model (i.e., MaxEnt) to simulate habitat distribution changes of the local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Feng ( 2015 ) found that suitable habitats were fragmented in central and northern Mabian Nature Reserve. Unsuitable habitats might be caused by deforestation, road construction and livestock invasion (Feng, 2015 ; Zhang et al, 2018 ; Zhao et al, 2017 ). Fragmented suitable habitats and unsuitable habitats could influence the habitat selection and migration of giant panda.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Feng ( 2015 ) found that suitable habitats were fragmented in central and northern Mabian Nature Reserve. Unsuitable habitats might be caused by deforestation, road construction and livestock invasion (Feng, 2015 ; Zhang et al, 2018 ; Zhao et al, 2017 ). Fragmented suitable habitats and unsuitable habitats could influence the habitat selection and migration of giant panda.…”
Section: Discussionmentioning
confidence: 99%
“…Feng (2015) found that suitable habitats were fragmented in central and northern Mabian Nature Reserve. Unsuitable habitats might be caused by deforestation, road construction and livestock invasion (Feng, 2015;Zhang et al, 2018;Zhao et al, 2017).…”
Section: Genetic Health Assessment Of Populationsmentioning
confidence: 99%
“…To identify a subset of environmental variables with minimal multicollinearity, we calculated the pairwise Pearson correlation coefficients for all 22 environmental variables. For a pair of variables with a correlation coefficient |r| > 0.7, we tested all environmental variables in a pairwise way, and retained the variable with the lowest variance inflation factor (VIF) in each pair of variables [ 25 , 40 , 41 , 42 ]. Finally, six variables were used for constructing the SDMs: isothermality (Bio03), annual precipitation (Bio12), precipitation seasonality (Bio15), elevation, slope, and aspect.…”
Section: Methodsmentioning
confidence: 99%
“…This finding also echoes previous studies. In recent years the implementation of ecological restoration projects has largely promoted the transfer of rural to urban populations, reduced the rural population in mountainous areas to a certain extent, contributing to restoration of giant panda habitats (Zhang et al, 2018;Li et al, 2019;Han et al, 2022;Li and Song, 2022).…”
Section: Nighttime Light Dynamics and Habitat Fragmentationmentioning
confidence: 99%